2005
DOI: 10.1021/jp046549s
|View full text |Cite
|
Sign up to set email alerts
|

Stable Superhydrophobic Surface via Carbon Nanotubes Coated with a ZnO Thin Film

Abstract: We report the formation of a stable superhydrophobic surface via aligned carbon nanotubes (CNTs) coated with a zinc oxide (ZnO) thin film. The CNT template was synthesized by chemical vapor deposition on an Fe-N catalyst layer. The ZnO film, with a low surface energy, was deposited on the CNT template by the filtered cathodic vacuum arc technique. Contact angle measurement reveals that the surface of the ZnO-coated CNTs is superhydrophobic with water contact angle of 159 degrees . Unlike the uncoated CNTs surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
157
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(177 citation statements)
references
References 14 publications
7
157
2
3
Order By: Relevance
“…The similar FT-IR spectrum results for W15 surface before and after 240 hours of UV exposure were achieved. Therefore, we concluded the PP-HMDSO coating deposited on anodized and water treated aluminum surfaces have a relatively good stability against UV degradation compared to other research work done by Hugan et al [148] that showed the superhydrophobic coating had changed to hydrophilic coating after 8 hours of UV exposure. It should be noted that 240 hours of exposure in the mentioned apparatus is equivalent to about six months of natural exposure in Canada (see section III.3.6).…”
Section: V-1-effect Of Uv Radiations On Hmdso Thin Filmsmentioning
confidence: 49%
“…The similar FT-IR spectrum results for W15 surface before and after 240 hours of UV exposure were achieved. Therefore, we concluded the PP-HMDSO coating deposited on anodized and water treated aluminum surfaces have a relatively good stability against UV degradation compared to other research work done by Hugan et al [148] that showed the superhydrophobic coating had changed to hydrophilic coating after 8 hours of UV exposure. It should be noted that 240 hours of exposure in the mentioned apparatus is equivalent to about six months of natural exposure in Canada (see section III.3.6).…”
Section: V-1-effect Of Uv Radiations On Hmdso Thin Filmsmentioning
confidence: 49%
“…Hydrophobic materials are commonly applied onto textured surfaces to promote hydrophobicity. Teflon [116,117], PFOS (perfluoro-octane sulfonates) [118], PDMS (polydimethylsiloxane) [119], and CNTs (carbon nanotubes) [120,121,122] are representative examples. CVD (chemical vapor deposition), PVD (plasma vapor deposition), and electrochemical deposition techniques are commonly used to coat these materials.…”
Section: Dwc On Textured Surfacementioning
confidence: 99%
“…Shang et al prepared a transparent, superhydrophobic, silica-based surface film by introducing a nano-scale rough surface [1]. Huang et al confirmed that a superhydrophobic surface can be achieved by aligned carbon nanotubes coated with a thin zinc oxide film [2]. Lee and Michielson enhanced the surface hydrophobicity of nylon flock fabric by grafting with poly(acrylic acid) and 1H-1H-perfluorooctyl-amine [3].…”
Section: Introductionmentioning
confidence: 99%